A Prospective Study on Effect of High Dose of Steroid on Platelet Count in Acute Stage of Dengue Fever with Thrombocytopenia (Academia Journal of Medicine, 2020)
Background: Dengue was the second disease after “yellow fever” that was shown to be caused by virus. The present study was conducted to assess effect of steroid on platelet count in acute stage of dengue fever. Subjects and Methods: 112 patients of dengue fever were divided into 2 groups. Group I was prescribed intravenous dexamethasone 8 mg initially followed by 4 mg every 8 hours thereafter for 4 days and group II patients was given only IV fluids and antipyretics. Results: Group I had 30 males and 26 females and group II had 25 males and 27 females. The mean platelet count (thousands) in day 1 was 29846.8 and 32442.4 in group I and group II respectively, on day 2 was 56003.4 and 44284.6, on day 3 was 78012.6 and 74224.6 and on day 4 was 126124.8 and 114620.4. The difference between both groups was non- significant (P> 0.05). Conclusion: High dose dexamethasone regimen was not effective in achieving a higher rise in the platelet count in the acute stage of dengue fever.
Keywords: Dexamethasone; dengue; Platelet